2011
DOI: 10.1149/1.3592876
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance of GaN-Based LEDs by Covering Top C-Plane of Patterned Sapphire Substrate with Oxide Layer

Abstract: Patterned sapphire substrate (PSS) has been used to improve both internal quantum efficiency (IQE) and light extraction efficiency (LEE) of GaN-based light-emitting diodes (LEDs). In this study, two kinds of periodic triangle pyramidal array PSSs were fabricated by wet etching. (1) "CPSS" was pyramid with a flat top c-plane, and (2) "OPSS" was pyramid with an oxide-covered top c-plane. It was found that the output power of OPSS was 29.0 mW, which was 6.2% higher than that of CPSS. This is because the GaN later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The MNPSS structure comprised a hexagonal pyramid with an oxide-covered top c-plane. 2,9 The height of pattern was 200-300 nm (measured by AFM), while the diameter of hemisphere oxide (LPD-SiO 2 ) was 250-300 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MNPSS structure comprised a hexagonal pyramid with an oxide-covered top c-plane. 2,9 The height of pattern was 200-300 nm (measured by AFM), while the diameter of hemisphere oxide (LPD-SiO 2 ) was 250-300 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the patterned sapphire substrate (PSS) (especially nano-sized PSS) has attracted much attention because it can improve both internal quantum efficiency (IQE) and light extraction efficiency (LEE). [1][2][3][4][5][6] This is because with increase in growth time, laterally grown GaN caused the threading dislocations to bend toward the patterns. However, it is still hard to control the indium fraction and the residual stress during the epitaxial process.…”
mentioning
confidence: 99%
“…In order to improve the crystalline quality of GaN-based epitaxial layers at the tip of the pattern, various growth techniques have been proposed, for example by Shen et al who used plasma treatment to create a slightly roughened surface pattern, which not only suppressed lateral growth from the sidewall of the pattern, but also enhanced vertical growth from the mesa and groove of the pattern [21]. Lin et al reported the preparation of a pyramid with an oxide-covered top c-plane (OPSS) [22]. The nucleation layer between the sapphire substrate and the GaN layer is the key to the dislocation density.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] For example, Lin et al, 21 investigating the effect of an oxide layer on PSS (OPSS) on the performance of LEDs, reported that the output power of OPSS LEDs was 6.2% higher z E-mail: tyseong@korea.ac.kr than that of conventional LEDs. In addition, Chang et al, 22 investigating the effect of a high-temperature (HT) (1050…”
mentioning
confidence: 99%
“…20 Thus, to further improve the crystallinity of GaN layers, the surface characteristics of PSS were modified by using an oxide layer 21 or an AlN nucleation layer. [22][23][24] For example, Lin et al, 21 investigating the effect of an oxide layer on PSS (OPSS) on the performance of LEDs, reported that the output power of OPSS LEDs was 6.2% higher z E-mail: tyseong@korea.ac.kr than that of conventional LEDs. In addition, Chang et al, 22 investigating the effect of a high-temperature (HT) (1050…”
mentioning
confidence: 99%